2017
DOI: 10.1002/joc.5365
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic to large‐scale drivers of minimum temperature variability in Australia – long‐term changes

Abstract: This study documents the importance, and changes in the importance, of a suite of synoptic to large‐scale drivers of minimum temperature variability across the Australian region. The drivers investigated are the El Niño – Southern Oscillation (ENSO) as measured by the Southern Oscillation Index, atmospheric blocking, the Southern Annular Mode, and the position and intensity of the subtropical ridge. In most regions, individual drivers generally account for between about 5 and 10% of the interannual variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
(154 reference statements)
0
10
0
Order By: Relevance
“…The gross increase in the observed annual temperature is attributed to the increase in the minimum temperature. Many researchers have reported that the minimum temperature rises more than the maximum (Bayramzadeh et al, 2018, Crimp et al, 2018, Gross et al, 2018, Scott et al, 2017 The minimum temperature incremental increase is more evident than that of the maximum. The results are of good agreement with the results by (Asfaw et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The gross increase in the observed annual temperature is attributed to the increase in the minimum temperature. Many researchers have reported that the minimum temperature rises more than the maximum (Bayramzadeh et al, 2018, Crimp et al, 2018, Gross et al, 2018, Scott et al, 2017 The minimum temperature incremental increase is more evident than that of the maximum. The results are of good agreement with the results by (Asfaw et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Australia, bounded by the Indian, South Pacific and Southern Oceans, lies between 10°S and 44°S latitude, and 112°E and 154°E longitude. Strongest drivers of temperature variability over the continent include the El Niño Southern Oscillation (ENSO) (Trenberth, 1997; Power et al ., 1999), the Southern Annular Mode (SAM), atmospheric blocking, and the subtropical ridge (Fierro and Leslie, 2014; Crimp et al ., 2018). Southwestern and southern regions of Australia are impacted by mid‐latitude cyclones (westerly waves; cold fronts), affecting southern parts of Australia year round.…”
Section: Methodsmentioning
confidence: 99%
“…The SAM, which dominates SH circulation as a whole, significantly affects Australian climate as the position of the westerlies changes (Rogers and van Loon, 1982; Marshall, 2003; Meneghini et al ., 2007). During a positive SAM, westerlies intensify and contract towards the poles, allowing easterly winds from the Tasman Sea to move over southern Australia (Hendon et al ., 2007; Crimp et al ., 2018). A positive SAM causes significant cooling and wet conditions over most of Australia (Gillett et al ., 2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations